Pengaruh Campuran Kangkung Afkir dan Ampas Tahu Terfermentasi Terhadap Konsumsi, Kecernaan Lemak Kasar dan Serat Kasar Ternak Babi Peranakan Landrace Fase Grower-Finisher - Payong, Siprianus; Dodu, Tagu; Suryani, Ni Nengah (Yayasan Sumber Daya Manusia Cerdas, 2024)
The study aimed at evaluating the effect of using rejected water spinach and fermented tofu dregs in pork rations on consumption, digestibility of crude fat and crude fiber. This study used 12 landrace pigs in the grower-finisher phase aged 3-4 months with an initial weight of 30-48 kg and an average of 14.25 (CV=15.47%). This study used a randomized block design (RBD) with 4 treatments and 3 replications. The treatments were R0 = basal ration (control), R1 = ration containing 10% mixture of Rejected water Spinach and fermented tofu dregs, R2 = ration containing 15% mixture of Rejected water Spinach and fermented tofu dregs, R3 = ration containing 20% mixture of Rejected water Spinach and dregs fermented tofu. The variables studied were consumption, digestibility of crude fat and crude fiber. The results of the analysis showed that the treatment had no significant effect (P>0.05) on crude fat consumption, crude fat digestibility and crude fiber digestibility, as well as increasing crude fiber consumption very significantly (P<0.01). It can be concluded that the use of a mixture of rejected kale and fermented tofu dregs up to 20% increased crude fiber consumption but had no effect on crude fat consumption, crude fat digestibility and crude fiber digestibility. A mixture of rejected kale and tofu dregs can be used up to 20% in the ration.